An Ethnolinguistic Analysis of Lexicons and Cultural Meaning in the Gebug Ende Ritual in Seraya Village, Karangasem Regency - Veranita Helmawan; I Gede Budasi; Made Aryawan Adijaya (Krinok:Jurnal Linguistik Budaya, 2026)
This research aims to identify the lexicons used in the Gebug Ende ritual in Seraya Village, Karangasem Regency, and to analyze the cultural meanings embedded in those lexicons. The study is based on the declining understanding of ritual lexicons among the younger generation of the Seraya community, which poses a challenge to the preservation of the Balinese language and local cultural heritage. This study employed an ethnographic approach. The data were collected through non-participant observation and in-depth interviews with Penglingsir (a respected senior figure), ritual practitioners, and Jero Pendalem (a traditional ritual custodian), selected through purposive sampling. The findings reveal that there are 37 lexicons used in the Gebug Ende ritual, categorized into four groups: 20 lexicons related to the ritual stages, 9 lexicons related to ritual tools, 4 lexicons related to ritual participants, and 4 lexicons related to ritual offerings. The identified lexicons represent the Seraya community's spiritual beliefs, cultural identity, local wisdom, and the values of harmony among humans, nature, and the divine. In conclusion, documenting and understanding the lexicons used in the Gebug Ende ritual plays a significant role in preserving the Balinese language, strengthening cultural identity, and supporting the continuity of this traditional ritual for future generations.